Genetic transformation of rice cv. Ciherang using double T-DNA vector harboring cry1Ab gene - Sulistyowati, Yuli; Rachmat, Agus; Zahra, Fatimah; Rahmawati, Syamsidah; Nugroho, Satya (ANNALES BOGORIENSES, 2011)
Rice stem borer (Scirpophaga sp.) is considered as one of the primary pests causing yield decrease in Indonesia. Genetic engineering is considered as one of the most effective way to improve the resistance of rice plants to yellow stem borer since no resistance gene has been found in rice and its wild relatives. A double T-DNA binary vector p2TDNAcryIAb wich carry two independent T-DNA was used to transform Indonesian elite rice cv Ciherang using Agrobacterium-mediated transformation to generate transgenic rice that free from selectable marker genes. One T-DNA containing a selectable marker hygromycin phosphotransferase (hpt) gene and the other carrying the cry1Ab gene. As many as 37 putative transgenic plants from 14 embryos were generated. PCR analysis demonstrated that 22 out of 37 putative transgenic rice contain cry1Ab gene. All Ciherang rice carrying the cry1Ab gene expressing Cry1Ab protein as shown by the immunostrip assay. Further work will be carried out to determine the transgenes copy number, to select marker free transgenic rice, and to evaluate the resistance of transgenic rice against neonates larvae of yellow stem borer.Keyword: double T-DNA, transgenic rice, Cry1Ab, transformation